ChemInform Abstract: Molybdenum(VI) Dioxo Complexes for the Epoxidation of Allylic Alcohols and Olefins. Issue 16 (April 2015) - Pandhare, Swati L.; Jadhao, Rajesh R.; Puranik, Vedavati G.; Joshi, Pranaya V.; Capet, Frederic; Dongare, Mohan K.; Umbarkar, Shubhangi B.; Michon, Christophe; Agbossou‐Niedercorn, Francine
Abstract A newly synthesized molybdenum(VI) dioxo complex is used as a catalyst for the epoxidation of allylic alcohols and olefins.